ANALISA PENEMPATAN LIGHTNING ARRESTER SESUDAH CUT OUT UNTUK MENGURANGI GANGGUAN TEGANGAN LEBIH PADA TRAFO KL 0074 DI PT. PLN (Persero) ULP KLUNGKUNG - Irwan Kurnia Yulianto; I Wayan Rinas; I Made Suartika (Jurnal SPEKTRUM, 2021)
Where it was recorded that according to BMKG data in 2019 in East Bali there were 15,000-30,000 lightning strikes. This gives the potential for, lightning strike on a 20 kV distribution linewhich is quite high. This connection will cause interference to the feeder if the lightning arresteris placed on the distribution transformer incorrectly. The equepment used to protect equipmentfrom lightning surge distrubances, one of which is a lightning arrester. The lightning arresterused in the KL 0074 substation is in place after the cut out. The Losan medium-voltage aerialfeeder is conncected by an A3CS cable for 8.5 km and an MVTIC cable for a distance of 2.02km which is connected to the KL 0074 substation. The distance between the KL 0074transformer and the lightning arrester is 3.75 meters, so it needs to be examined further to findout whether the protection generated by the lightning arrester is optimal or not. Theeresulttofftheanalysissshowwthatttheelightning arrester with an instalation distance of 0.34 meters from thetransformer is still able to cut the lightning surge, with the resulting splash voltage of 124.977.4Volts but the spark voltage is within the tolerance limit of the 125 kV lightning arrester splashvoltage.,